«Due voci dialogano». Dissonanza e forma dell’Ospite ingrato - Peluso, Sabatino (L'ospite ingrato, 2025)
Franco Fortini’s work includes many hybrid or unclassifiable books: and l’Ospite ingrato, which straddles the line between autobiography, essay, and poetry, is exemplary in this sense, but it also serves an important function as an intellectual manifesto. Starting from a discussion of these aspects, and moving on to a comparison with the main critical positions, the essay examines the particular “form” of this book by Fortini and attempts to reinterpret it in light of the important link that can be traced between the author’s formal work and his ethical-political vision.